2020
DOI: 10.1108/ijilt-10-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

Remote teaching for equal and inclusive education in rural areas? An analysis of teachers’ perspectives on remote teaching

Abstract: PurposeThe aim of this study is to explore equality and inclusion as an aspect of remote teaching in rural areas. Moreover, the aim is to explore teachers' pedagogical digital competence (PDC) and school organizational support as conditions for developing remote teaching.Design/methodology/approachA mixed method approach with both qualitative and quantitative data was used.FindingsAccording to this study, remote teaching can solve many problems for school organizations and offer pupils new opportunities to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 18 publications
(29 reference statements)
4
41
0
5
Order By: Relevance
“…Nevertheless, remote teaching is not a new idea. Existing research findings indicated that online remote teaching has been reported for equal and inclusive education in rural areas in various countries [11][12][13]. A second mode of remote teaching was also applied when schools are closed or inaccessible due to a natural disaster [14,15] or other emergency, for example the war crisis in Syria [16].…”
Section: Emergency Remote Teachingmentioning
confidence: 99%
“…Nevertheless, remote teaching is not a new idea. Existing research findings indicated that online remote teaching has been reported for equal and inclusive education in rural areas in various countries [11][12][13]. A second mode of remote teaching was also applied when schools are closed or inaccessible due to a natural disaster [14,15] or other emergency, for example the war crisis in Syria [16].…”
Section: Emergency Remote Teachingmentioning
confidence: 99%
“…After the pandemic, education at all levels will no longer be the same. MOOCs have a number of advantages and they can significantly contribute to teachers' professional development, through their participation in teachers' learning communities (Stenman & Pettersson, 2020) professional learning networks and school networks as well (Hilli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tillåtna skolämnen bestämdes till moderna språk, modersmål, samiska i sameskolan och teckenspråk, samt för att ge elever studiehandledning på modersmål och integrerad samisk undervisning (Skollagen, 2010:800). I realiteten bedrivs dock fjärrundervisning i en vidare omfattning än så, då fjärrundervisning för många skolor runt om i Sverige ses som ett sätt att hantera faktiska behov (se t ex Öjefors-Stark, 2019, Stenman & Pettersson, 2020). Det kan till exempel handla om att tillämpa fjärrundervisning i andra ämnen än de som tillåts, inte tillåten användning av entreprenad, det kan även handla om elever som deltar i fjärrundervisning hemifrån eller en distansutbildning, som innebär kommunikation på annat sätt än i realtid (Skolverket, 2018).…”
Section: Skolans Digitaliseringunclassified
“…För fjärrundervisning utgör digitalisering och tillgång till digitala teknologier, som framgår i denna studie, en viktig förutsättning för att hantera de pedagogiska behov skolan har (se även Millet, 2012), men där tekniken i sig inte utgör någon slags fristående satsning eller en lösning. Istället fungerar strävan om en tillgänglig, högkvalitativ och likvärdig undervisning som ett viktigt mål, som ger digitaliseringen en pedagogisk betydelse, då digital teknik så att säga öppnar upp en väg för att uppnå likvärdighet i skolan oavsett geografisk plats (Pettersson, 2009;Stenman & Pettersson, 2020). Detta tydliggörs även i denna studie där lärarna, trots inledande oro avseende teknikanvändning, i och med fjärrundervisningen har ett tydligt pedagogiskt objekt med digitalisering och teknikanvändning.…”
Section: Fjärrundervisning -Ett Strategiskt Inslag I Skolans Digitaliunclassified